Akano and his Golden Ring - Adeleke, Dapo (Literamed Publications Ltd, 2007)
Abebi is hated by the entire village for marrying Ajao, her father's slave. Ajao could not afford to cater for his family as a result of this and he is mocked by the villagers. Abebi is accosted on a certain day on the farm by a bearded old man who gives her a ring meant for Akano, their son's protection when he grows up...
Keywords: Juvenile Fiction / Adventure